Global burden of Type 2 Diabetes Mellitus attributable to dietary risks in elderly adults: insights from the Global Burden of Disease study 2021 - Tang, Yiting; Chen, Yupeng; Zhou, Yang; Wu, Bingrong; Zhang, Shan; Gong, Yanbing; Ni, Qing (Frontiers in Nutrition, 2025)
BackgroundType 2 Diabetes Mellitus (T2DM) poses a significant global health challenge, particularly among elderly adults. Dietary risk factors, such as high consumption of processed meats and sugar-sweetened beverages and low intake of whole grains and fruits, play a critical role in the burden of T2DM. This study aims to comprehensively quantify the global burden of T2DM attributable to dietary risks among elderly adults, identify significant dietary risk factors driving disease burden, and evaluate temporal, regional, and demographic variations to inform targeted public health strategies and interventions for reducing the impact of T2DM.MethodsThis study utilized data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 to assess T2DM burden attributable to dietary risks among adults aged 65 years and older across 204 countries and territories. Metrics included age-standardized mortality rates (ASMR) and disability-adjusted life-year rates (ASDR). Dietary risk factors analyzed included low intake of whole grains, fruits, vegetables, and fiber, as well as high intake of processed meat, red meat, and sugar-sweetened beverages. Joinpoint regression and decomposition analyses were performed to examine temporal trends and drivers of changes by region, SDI level, sex, and age.ResultsIn 2021, dietary risks accounted for 23.61% of T2DM-related deaths and 24.85% of DALYs among elderly adults. ASMR showed a slight decline globally (AAPC: −0.08), while ASDR exhibited a significant upward trend (AAPC: +0.7) from 1990 to 2021. High SDI regions demonstrated decreasing ASMR but persistent DALYs due to prolonged survival with complications. Conversely, low and middle SDI regions exhibited rapid increases in ASMR and ASDR, driven by dietary transitions and limited healthcare resources. Males consistently bore a higher burden than females, with pronounced disparities in low and middle SDI regions. Aging and population growth were the primary drivers of the increasing burden globally.ConclusionThis study underscores the substantial burden of T2DM attributable to dietary risks among elderly adults and highlights significant regional and demographic disparities. Targeted public health interventions, personalized nutritional strategies, and improved healthcare access are essential to mitigate this burden. Future research should explore the impact of emerging dietary trends and precision nutrition on T2DM prevention and management.